Uncertainty and Investment : The Financial Intermediary Balance Sheet Channel - Chen, Sophia (Washington, D.C. : International Monetary Fund, 2015)
Rollover risk imposes market discipline on banks' risk-taking behavior but it can be socially costly. I present a two-sided model in which a bank simultaneously lends to a firm and borrows from the short-term funding market. When the bank is capital constrained, uncertainty in asset quality and rollover risk create a negative externality that spills over to the real economy by ex ante credit contraction. Macroprudential and monetary policies can be used to reduce the social cost of market discipline and improve efficiency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United Kingdom